2016
DOI: 10.3748/wjg.v22.i42.9394
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome evaluation using computed tomography colonography

Abstract: AIMTo evaluate the morphology of the colon in patients with irritable bowel syndrome (IBS) by using computed tomography colonography (CTC).METHODSTwelve patients with diarrhea type IBS (IBS-D), 13 patients with constipation type IBS (IBS-C), 12 patients with functional constipation (FC) and 14 control patients underwent colonoscopy following CTC. The lengths of the rectosigmoid colon, transverse colon and the total colon were measured. The diameters of the rectum, sigmoid colon, descending colon, transverse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first study to show that bowel habits (defecation frequency) clearly correlate with colon length in a cohort study. A previous case–control study ( n = 51) utilizing CT colonography reported that patients with functional constipation had a significantly longer colon compared with diarrhea type IBS or control patients [ 22 ]. These results suggest that defecation frequency is associated with colon length and are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to show that bowel habits (defecation frequency) clearly correlate with colon length in a cohort study. A previous case–control study ( n = 51) utilizing CT colonography reported that patients with functional constipation had a significantly longer colon compared with diarrhea type IBS or control patients [ 22 ]. These results suggest that defecation frequency is associated with colon length and are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several researchers have measured colon length using CT colonography to identify the cause of incomplete colonoscopy [ 17 ], colon length difference compared with colonoscopy [ 18 , 19 ], positional alteration of the colon length [ 20 ] and the correlation of colon anatomy with age, gender and body mass index [ 21 ]. Ohgo et al reported that the entire colon in patients with functional constipation was significantly longer than patients with diarrhea-type irritable bowel syndrome (IBS) or control patients in a small-scale case–control study [ 22 ]. However, previous studies using CT colonography have not examined the association with gender, age, physique, a history of laparotomy and bowel habits, all possible contributory factors to colon length.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, region of interest (ROI) activation (such as the parietal region, prefrontal cortex, cerebellum, anterior cingulate cortex, insular cortex, and thalamus) differed significantly between the 40ml and 120-ml conditions, and between the 80-ml and 120-ml conditions (P < 0.05), among patients with IBS with anxiety or depression scores less than 9 points. 9…”
Section: Resultsmentioning
confidence: 99%
“…Ohgo, H et al (2016) 9 showed CT colonography might contribute the clarification of subtypes of IBS.…”
Section: Participantsmentioning
confidence: 99%
“…The prior selection is based on the studies by Gilroy et al [ 41 ] and Ohgo et al [ 42 ], where the average diameter of the large intestine is reported to be cm, with standard deviation cm, on the interval cm. Following the idea of drawing sample frequencies, the intestine diameter, , is drawn from either a uniform distribution or a truncated Gaussian distribution with , , , and .…”
Section: Resultsmentioning
confidence: 99%